Millar Carvacho, René. La Inquisición de Lima. Signos de su decadencia, 1726-1750. Santiago de Chile: DIBAM, LOM Ediciones, Centro de Investigaciones Diego Barros Arana, 2004, 196 pp. - Guibovich Pérez, Pedro M. (2006)
No presenta resumen